Pengaruh Kecenderungan Celebrity Worship Terhadap Subjective Well Being Pada Penggemar K-Pop Dewasa Awal di Makassar - Anisah Mubarakah; Kurniati Zainuddin; Perdana Kusuma (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
K-Pop music has become a global phenomenon that influences many aspects of its fans' lives. Since liking K-Pop, many fans have felt happiness and well-being or subjective well-being. Subjective well-being is an evaluation of life satisfaction carried out by individuals, which includes life satisfaction, happiness and pleasant experiences. This research aims to determine the influence of celebrity worship tendencies on subjective well-being among K-Pop fans in Makassar. This research used quantitative methods with research respondents totaling 142 early adult K-Pop fans in Makassar City aged 18 to 25 years. The measuring instruments used in this research were the CAS scale with a reliability of 0.910, the SWLS scale with a reliability of 0.840 and the SPANE scale with a reliability value of 0.766 for positive affect and 0.738 for negative affect. Test the hypothesis using a Spearman rank using the SPSS version 26.0 application with a result of sig = 0.037. The results of this study show that there is no influence between social entertainment, intense personal and borderline pathological celebrity worship on subjective well-being. The implication of this research is that K-Pop fans are expected to pay attention to the limits of idolizing celebrities to prevent obsessions that are detrimental to subjective well-being, as well as contributing to theory and practice related to the phenomenon of celebrity worship in the context of K-Pop fans.